Capital dames : the Civil War and the women of Washington, 1848-1868 - Roberts, Cokie (Harper/HarperCollins, 2015)
A companion to the best-selling Founding Mothers and Ladies of Liberty documents the experiences, influence and contributions of women during the American Civil War.